Erythropoietin for the prevention of postoperative neurocognitive disorder in older adult patients undergoing total joint arthroplasty: a randomized controlled study - Eun Jung Kim; Kwan Kyu Park; Su Youn Choi; Hyang Mi Ju; Tae Lim Kim; Jeongmin Kim; Soo Yeon Kim; Bon-Nyeo Koo (BMC Anesthesiology)
Abstract Background Post-operative delirium (PD) is a common post-operative complication with significant clinical and financial impacts on patients. Erythropoietin (EPO), a multi-functional glycoprotein hormone, exhibits erythropoietic and non-erythropoietic anti-inflammatory properties. This study aimed to determine the role of perioperative EPO administration in the development of postoperative delirium in older adult patients undergoing total joint arthroplasty. Methods Seventy-one patients (> 65 years old) scheduled for total joint arthroplasty were randomly assigned to two groups: EPO-treated (EPO, n = 35) and placebo (control, n = 36). All patients completed the Mini Mental State Examination (MMSE) pre-operatively and on post-operative day (POD) 2. The confusion assessment method (CAM) was used to assess the patients until discharge (POD 5). Serum C-reactive protein (CRP) and inflammatory cytokine levels were measured and compared pre- and post-operatively. The development of delirium and cognitive dysfunction was evaluated post-operatively. Results One patient in the control group developed delirium on POD 2 (3.2%), whereas no patient in the EPO group developed PD (0% vs. 3.2%, p = 0.500). Post-operatively there was no significant difference in MMSE scores between groups. Both groups showed increases in pro- and anti-inflammatory cytokine levels, with no significant differences. Similarly, CRP levels, neutrophil/lymphocyte ratio (NLR), and platelet/lymphocyte ratio (PLR) showed no intergroup differences in post-operative inflammatory responses. Conclusions Perioperative EPO reduced the incidence of post-operative delirium, although not statistically significant, with no differences in post-operative cognitive function and inflammatory responses. Trial registration The trial was registered on December 12, 2023 at http//clinicaltrials.gov, registration number NCT06178835.